2010
DOI: 10.1111/j.1472-4642.2010.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

BIODIVERSITY RESEARCH: Native‐exotic species richness relationships across spatial scales and biotic homogenization in wetland plant communities of Illinois, USA

Abstract: Aim  To examine native‐exotic species richness relationships across spatial scales and corresponding biotic homogenization in wetland plant communities. Location  Illinois, USA. Methods  We analysed the native‐exotic species richness relationship for vascular plants at three spatial scales (small, 0.25 m2 of sample area; medium, 1 m2 of sample area; large, 5 m2 of sample area) in 103 wetlands across Illinois. At each scale, Spearman’s correlation coefficient between native and exotic richness was calculated. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 61 publications
4
36
1
Order By: Relevance
“…Beta diversity of native and alien plant species results from environmental heterogeneity in space, time, resources, disturbance regime and niche differences among species (Loreau 2000;Gabriel et al 2006). In addition, higher beta diversity of both native and alien species can ensue from greater spatial heterogeneity in resource availability and disturbance regime (Davies et al 2005;Belote et al 2008;Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta diversity of native and alien plant species results from environmental heterogeneity in space, time, resources, disturbance regime and niche differences among species (Loreau 2000;Gabriel et al 2006). In addition, higher beta diversity of both native and alien species can ensue from greater spatial heterogeneity in resource availability and disturbance regime (Davies et al 2005;Belote et al 2008;Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, researchers have been concerned with cumulative diversity (gamma diversity) when studying diversity-invasibility relationships (e.g. Stohlgren et al 1999;Deutschewitz et al 2003;Gilbert and Lechowicz 2005;Davies et al 2007;Belote et al 2008;Chen et al 2010), whereas the model of Shea and Chesson (2002) only accounted for patterns of mean diversity (alpha diversity).…”
Section: Introductionmentioning
confidence: 99%
“…In their review of the effects of the composition and configuration of the landscape on the distribution of introduced species, Vilà and Ibàñez (2011) confirmed that there are more alien species at habitat edges than in the interior of fragments, and in numerous localized studies, proximities to other land uses are important factors that contribute to higher incidence of introduced species invasions (Chen et al 2010;Meekins and McCarthy 2001;Moser et al 2009;Ohlemüller et al 2006;Schulte et al 2011;Yates et al 2004). In Europe, those habitats with the greatest proportion of alien species were either man-made or those subject to frequent disturbance by flooding (Chytrý et al 2008).…”
Section: Levels Of Fragmentation and Introduced Species Distributionmentioning
confidence: 90%
“…These authors analyzed the relationship between archaeophytes and neophytes rather than natives and found that archaeophyte richness was the single best predictor for neophyte richness across the 33 habitat types they examined. Others have found no evidence of a relationship between native and introduced species (Ohlemüller et al 2006) or found that it does not hold true at the smallest scales (Chen et al 2010). Most studies surmise that positive correlations between native and introduced species richness indicate more about resource availability to all plant species, especially pulses of resources or short-term changes in resources-flooding, light (canopy gaps), temperature regimes, and events that alter soil nutrients (Chytrý et al 2008) Our analyses showed a positive, significant relationship between native and introduced species richness over the entire population of forested lands and for most intact forests over the various ecological provinces.…”
Section: Correlation Between Native and Introduced Speciesmentioning
confidence: 96%
See 1 more Smart Citation